Relationship between Constrictotermes cyphergaster and Inquiline Termites in the Cerrado (Isoptera: Termitidae) - Da Cunha, Hélida Ferreira; Costa, Diogo Andrade; Santo Filho, Kleber Do Espírito [UNESP]; Silva, Lucivânio Oliveira; Brandão, Divino (My University, 2003)
Constrictotermes cyphergaster builds arboreal nests in Cerrado sensu stricto of Brazil; inquiline termites and termitophiles frequently inhabit their nests. Measurements of the nests and the support trees (nest width and diameter; tree trunk circumference and inclination), colony size of C. cyphergaster and of Inquilinitermes and number of termitophiles were studied at the Parque Estadual da Serra de Caldas Novas. These variables were subjected to a Principal Component Analysis, producing four principal components. The first principal component refers to a multidimensional axis of nest size, encompassing variables related to nest and colony size, such as abundance per caste of C. cyphergaster and I. microcerus, number of termitophile species and the measurements of the nest. The number of soldiers and workers of C. cyphergaster and soldiers of Inquilinitermes increased proportionally to the axis of nest size, while the number of Inquilinitermes workers increased more quickly then the increase in the nest size. Both Inquilinitermes occurred mainly in larger nests. Almost half of the nests (47,5%) were inhabited by I. microcerus and 10% by I. fur.
Keywords: Constrictotermes; Inquilinitermes; Inquilinitermes microcerus; Isoptera; Termitidae